(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article is devoted to the theoretical substantiation of the problems of improving the investment policy of recipient countries in the conditions of digitalization of economic processes and determining the strategic priorities of investment policy in the digital economy.